Perpetuation of gender discrimination in Pakistani society: results from a scoping review and qualitative study conducted in three provinces of Pakistan - Tazeen Saeed Ali; Shahnaz Shahid Ali; Sanober Nadeem; Zahid Memon; Sajid Soofi; Falak Madhani; Yasmin Karim; Shah Mohammad; Zulfiqar Ahmed Bhutta (BMC, 2022)
Abstract Background Gender discrimination is any unequal treatment of a person based on their sex. Women and girls are most likely to experience the negative impact of gender discrimination. The aim of this study is to assess the factors that influence gender discrimination in Pakistan, and its impact on women's life. Methods A mixed method approach was used in the study in which a systematic review was done in phase one to explore the themes on gender discrimination, and qualitative interviews were conducted in phase two to explore the perception of people regarding gender discrimination. The qualitative interviews (in-depth interviews and focus group discussions) were conducted from married men and women, adolescent boys and girls, Healthcare Professionals (HCPs), Lady Health Visitors (LHVs) and Community Midwives (CMWs). The qualitative interviews were analyzed both manually and electronically through QSR NVivo 10. The triangulation of data from the systematic review and qualitative interviews were done to explore the gender discrimination related issues in Pakistan. Results The six major themes have emerged from the systematic review and qualitative interviews. It includes (1) Status of a woman in the society (2) Gender inequality in health (3) Gender inequality in education (4) Gender inequality in employment (5) Gender biased social norms and cultural practices and (6) Micro and macro level recommendations. In addition, a woman is often viewed as a sexual object and dependent being who lacks self identity unless being married. Furthermore, women are restricted to household and child rearing responsibilities and are often neglected and forced to suppress self-expression. Likewise, men are viewed as dominant figures in lives of women who usually makes all family decisions. They are considered as financial providers and source of protection. Moreover, women face gender discrimination in many aspects of life including education and access to health care. Conclusion Gender discrimination is deeply rooted in the Pakistani society. To prevent gender discrimination, the entire society, especially women should be educated and gendered sensitized to improve the status of women in Pakistan.